Influenza – the passion of my academic research life - B. Brydak, Lidia (Przewodnik Lekarza/Guide for GPs, 2011)
Influenza is an acute infectious disease caused by viruses of the family Orthomyxoviridae, assuming an epidemic form at seasonal and irregular times. According to the WHO, every year approximately 5-25% of the world population suffers from influenza and about 1 million victims die. Flu vaccinations are the cheapest and most effective way to combat this serious respiratory pathogen but still, especially in Poland, people are not willing to use this form of prevention. Currently, the only new drugs for respiratory tract infections, recommended for the treatment and prevention of influenza infection type A and B are oseltamivir and zanamivir.